Dyslipidemia inhibits Toll-like receptor–induced activation of CD8α-negative dendritic cells and protective Th1 type immunity - Shamshiev, Abdijapar T. (The Rockefeller University Press, 2007)
Environmental factors, including diet, play a central role in influencing the balance of normal immune homeostasis; however, many of the cellular mechanisms maintaining this balance remain to be elucidated. Using mouse models of genetic and high-fat/cholesterol diet–induced dyslipidemia, we examined the influence of dyslipidemia on T cell and dendritic cell (DC) responses in vivo and in vitro. We show that dyslipidemia inhibited Toll-like receptor (TLR)–induced production of proinflammatory cytokines, including interleukin (IL)-12, IL-6, and tumor necrosis factor-α, as well as up-regulation of costimulatory molecules by CD8α(−) DCs, but not by CD8α(+) DCs, in vivo. Decreased DC activation profoundly influenced T helper (Th) cell responses, leading to impaired Th1 and enhanced Th2 responses. As a consequence of this immune modulation, host resistance to Leishmania major was compromised. We found that oxidized low-density lipoprotein (oxLDL) was the key active component responsible for this effect, as it could directly uncouple TLR-mediated signaling on CD8α(−) myeloid DCs and inhibit NF-κB nuclear translocation. These results show that a dyslipidemic microenvironment can directly interfere with DC responses to pathogen-derived signals and skew the development of T cell–mediated immunity.